2022
DOI: 10.1038/s41375-022-01612-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BCR::ABL1 transcript type on RT-qPCR amplification performance and molecular response to therapy

Abstract: Several studies have reported that chronic myeloid leukaemia (CML) patients expressing e14a2 BCR::ABL1 have a faster molecular response to therapy compared to patients expressing e13a2. To explore the reason for this difference we undertook a detailed technical comparison of the commonly used Europe Against Cancer (EAC) BCR::ABL1 reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) assay in European Treatment and Outcome Study (EUTOS) reference laboratories (n = 10). We found the amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Recently, a study comparing amplification according to the transcript type found that shorter e13a2 transcripts may be amplified more efficiently than e14a2 by RT-qPCR, possibly leading to an underestimation of the quantified values of the e14a2 transcript. [28][29][30][31] However, some reports showed better or similar molecular responses in patients expressing the e13a2 transcript than in patients expressing the e14a2 transcript. Thus, more data are needed to understand the significance and role of BCR::ABL1 transcript type.…”
Section: Therapeutic Advances In Hematologymentioning
confidence: 99%
“…Recently, a study comparing amplification according to the transcript type found that shorter e13a2 transcripts may be amplified more efficiently than e14a2 by RT-qPCR, possibly leading to an underestimation of the quantified values of the e14a2 transcript. [28][29][30][31] However, some reports showed better or similar molecular responses in patients expressing the e13a2 transcript than in patients expressing the e14a2 transcript. Thus, more data are needed to understand the significance and role of BCR::ABL1 transcript type.…”
Section: Therapeutic Advances In Hematologymentioning
confidence: 99%
“…The influence of the BCR::ABL1 transcript type in CML still remains controversial, also due to technical bias, which could be bypassed by turning into alternative technologies, such as digital PCR (dPCR). Further studies are warranted to clarify this issue [ 124 ]. Currently, prognostic scores and high-risk ACAs are the only widely used and validated factors for risk stratification of CP-CML patients at baseline [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The real-time quantitative PCR (RT-qPCR) assays employed to measure BCR::ABL1 mRNA levels appear to be able to amplify the e13a2 amplicon more efficiently than the e14a2 amplicon [120,123]. This discrepancy in amplification performance may be related to the difference in amplicon length generated by the RT-qPCR assay (the e14a2 amplicon is approximately twice as large as e13a2), although the sequence itself may also be important [124][125][126]. The reported data include patients treated with frontline TKI expressing the e13a2 or e14a2 transcript (whether alone or in co-expression with the e13a2).…”
Section: Transcript Typementioning
confidence: 99%
“…Most kits and LDTs use an RT-qPCR design that employs a pair of primers and a single probe to detect both e13a2 and e14a2 BCR::ABL1 cDNA without distinguishing between them. Recent evidence indicates that at least part of the observed differences in molecular response are explained by small differences in PCR amplification efficiency between the two transcript types, with the larger e14a2 amplifying less efficiently and thereby giving the appearance of a superior response [ 109 111 ]. Results from transcript-specific assays may also be influenced by differences in amplicon size.…”
Section: Molecular Monitoring Of Measurable Residual Diseasementioning
confidence: 99%
“…Results from transcript-specific assays may also be influenced by differences in amplicon size. From a technical perspective, these differences may be overcome by using RT-dPCR, which is inherently more tolerant to factors that influence RT-qPCR efficiency [ 111 ]. The differences observed by RT-qPCR, however, are small compared to the natural variation in test results, do not translate into inferior outcomes [ 112 ] and are believed to have minimal effect on the management of individual patients [ 110 ].…”
Section: Molecular Monitoring Of Measurable Residual Diseasementioning
confidence: 99%